Leiomyoma with intracytoplasmic inclusion bodies in the oral cavity: an uncommon histological finding - Oliveira, Denise Hélen Imaculada Pereira de; Nascimento, Marcelo Anderson Barbosa; Queiroz, Lélia Maria Guedes; Pinto, Leão Pereira; Souza, Lélia Batista de (Journal of Oral Diagnosis, 2018)
Leiomyomas are benign tumors that arise from the smooth musculature and can occur in any part of the body where these muscles are present. However, leiomyomas of the oral cavity are rare because of the scarcity of smooth muscles at this site. We present a case of leiomyoma involving the tongue which exhibited a histological finding that is extremely rare in oral leiomyomas. Immunohistochemical analysis revealed positivity for smooth muscle actin (alfa - SMA, desmin) and negativity for S - 100, CD- 68 and CD34 protein. The main clinical and histopathological features of leiomyomas, as well as their differential diagnosis, were reviewed. Intracytoplasmic inclusion bodies have been found in uterine leiomyomas, in atypical (bizarre) leiomyomas and, occasionally, in epithelioid leiomyomas and leiomyosarcomas. However, a search of the main literature databases revealed no description of these inclusions in oral leiomyomas.